A thematic cluster analysis of parents' online discussions about fussy eating. Issue 2 (8th February 2022) - Markides, Brittany R.; Laws, Rachel; Hesketh, Kylie; Maddison, Ralph; Denney‐Wilson, Elizabeth; Campbell, Karen J.
Abstract: Food fussiness is associated with non‐responsive parent feeding practices, such as persuasive and instrumental feeding. Although most children described as 'fussy eaters' are likely exhibiting developmentally typical behaviours, up to half of the parents of children 2–5 years old express concerns. Concern for fussy eating may mediate the use of non‐responsive feeding practices and so must be addressed in parent feeding interventions. Therefore, it is critical to better understand parents' concerns and how they may relate to feeding practices. This study aimed to explore how parents' feeding practices and the social cognitive factors that may drive them clustered based on parents' concern for fussy eating. Data were collected from parent discussions of fussy eating on a Reddit forum (80, 366 posts). Latent Dirichlet allocation was used to identify discussions of fussy eating. Relevant posts (1542) made by users who identified as a parent of a fussy eater ( n = 630) underwent qualitative coding and thematic analysis. Five clusters of parents were identified, ranging in size from 53 to 189 users. These were primarily characterised by parents' degree of concern and feeding practices: (1) High concern, nonresponsive; (2) Concerned, nonresponsive; (3) Low concern, responsive; (4) Low concern, mixed strategies; (5) Low concern, indulgent. Parents who used responsive practices tended to be less concerned for fussy eating, have greater trust in their child's ability to self‐regulate hunger, have longer‐term feeding goals, and exhibit greater ability for personal self‐regulation. Future research should further examine how these constructs may be leveraged in parent feeding interventions. Key points: Parents using nonresponsive practices to manage fussy eating may have more concerns about fussy eating, less trust in their child's ability to self‐regulate hunger, shorter‐term feeding goals, and less developed self‐regulation skills. As most children described as "fussy eaters" are likely exhibiting developmentally typical behaviours, interventions addressing nutrition and feeding practices in early childhood should aim to alleviate parental concern for fussy eating, for example, by helping them recognise developmentally normal eating behaviours. Early childhood feeding interventions may also be enhanced by helping parents to develop long‐term feeding goals and improved self‐regulation skills in the context of their feeding practices.